Analgesic Quality Improvement in Paravertebral Blocks for Pediatric Nuss Procedure: An Exploratory Report on the Effects of Perineural Combined Glucocorticoids - Donham RN; Jin E; Caty MG; Thomas DA; Yuan C; Hollingsworth K; Zhang X; Yanez ND; Li J (Journal of Pain Research)
Rebecca N Donham,1,* Evan Jin,2,* Michael G Caty,3 Donna-Ann Thomas,2 Claire Yuan,4 Kamren Hollingsworth,2 Xuewei Zhang,2 N David Yanez,5 Jinlei Li2,* 1Alabama College of Osteopathic Medicine, Dothan, AL, USA; 2Department of Anesthesiology, Yale University School of Medicine, New Haven, CT, USA; 3Department of Surgery, Yale University School of Medicine, New Haven, CT, USA; 4Harvard University, Cambridge, MA, USA; 5Department of Anesthesiology, Duke University School of Medicine, Durham, NC, USA*These authors contributed equally to this workCorrespondence: Jinlei Li, Department of Anesthesiology, Yale University School of Medicine, 20 York Street, New Haven, CT, 06510, USA, Tel +1 (475) 434-4038, Email jinlei.li@yale.eduPurpose: Pectus excavatum repair using the Nuss procedure is associated with significant postoperative opioid consumption even in the presence of a continuous thoracic paravertebral block.Patients and Methods: A CQI project was initiated by adding combined glucocorticoids as perineural adjuvants to continuous thoracic paravertebral block. An electronic health record review of patients undergoing Nuss procedures by a single surgeon at a major academic children’s hospital from June 2013 to December 2021 was performed with no patients excluded. The patients received pre-incision continuous bilateral T4 paravertebral blocks preoperatively either with plain ropivacaine (standard group, N = 34) or with a combination of dexamethasone sodium phosphate (DXP) and methylprednisolone acetate (MPA) in addition to ropivacaine (experimental group, N = 10). The primary outcome studied was postoperative opioid consumption measured by oral morphine milligram equivalents (MME).Results: A total of 44 patients were included in the final analysis. The experimental group had 72% lower postoperative opioid usage than the standard group during the hospitalization (p < 0.001) with comparable pain scores and hospital length of stay and no increase in wound dehiscence or other complications.Conclusion: The addition of dexamethasone sodium phosphate and methylprednisolone acetate to continuous paravertebral blocks significantly decreased postoperative opioid consumption while maintaining comfort pain scores.Keywords: Nuss procedure, paravertebral, dexamethasone, methylprednisolone acetate